Sustainable intensification of smallholders’ maize-based mixed farming systems in Malawi - Mzumara, Edward; Kachali, Righteous; Homann-kee Tui, Sabine; Chiduwa, Mazvita; Liben, Feyera; Manda, Julius; Omondi, John; Tufa, Adane; Banda, Mcloyd; Botoman, Lester; Kamwana, Florence (2024)
Agronomic solutions for improved maize-legume intercropping systems, such as Mbili Mbili and Double Row Strip Cropping, integration of maize-legume rotations, combined with soil health and multi-purpose forages innovations for enhancing crop-livestock integration, have been validated as transformative for sustainable intensification. These systems support farmers—especially women and youth—to diversify and intensify farming activities, sustainably raising production on small plots, enhancing soil health, and ensuring profitability. By promoting legumes, often considered women’s crops, these innovations contribute to more inclusive decision-making and diversified diets. To enable uptake, farmers must have access to cash income to afford the inputs, including legume and forage seeds, organic and inorganic fertilizers, and the capacity to tailor agronomic advisories. Researchers engaging scaling partners through local-level platforms is one way to combine technical with socio-organizational innovations.